Analisis Resiko Postural Stress Pada Pekerja Di UD.XYZ Dengan Metode Rapid Upper Limb Assessment - Sie, Katherine Macella Silvanus; Valentino, Felix; Dearosa, Elvina Yunia; Rahardjo, Benedictus (Universitas Katolik Parahyangan, 2017)
UD.XYZ is a company that produce accessories for car. UD. XYZ have a factory that produce car accessories with small size like a safety belt accessories, car pillow, and tissue case. This research will be focus to analyze postural stress risk for worker that produce car accessories. This research is based on the complaints of workers who feel that some parts of their body sick and stiff because the work is a job that has a repetitive movement with almost the same position every time. The posture of the worker will be observed to determine whether the posture has a dangerous risk or not. The method used is the Rapid Upper Limb Assessment that will assess the workers posture from the waist to the head. Research indicates that the workers posture score is between 3 to 5 where the score is assessed to suggest that further investigation of posture is necessary. Giving a small desk to the worker and also socializing about good posture while working helps to improve the score from worker posture to 2 to 3 which means that posture can be used and minimize postural stress on the workers.